Pengaruh Strategi Pembelajaran Ekspositori Terhadap Pemahaman Siswa Pelajaran Aqidah Akhlak Kelas Viii Mts. An-Najah I Karduluk Sumenep Tahun 2016-2017 - Abd. Qadir (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2019)
Learning in general is the process of teaching and learning from the teacher to the student or vice versa. In the implementation of teacher learning, there is a need for a strategy. Learning strategies are basically real actions of the teacher or are the practice of teachers carrying out learning through certain ways that are considered more effective and efficient. One of the strategies that teachers can do is expository strategies. Among the subjects or fields of study in MTs. An-Najah I Karduluk Pragaan Sumenep are the subjects of aqidah akhlak. One form of demand for professionalism of aqidah akhlak teachers is to be able to implement expository learning strategies to increase student understanding. The study used a quantitative approach with a sample of 57 students. The data collection that the author uses is to distribute the questionnaire to all respondents. While observation and documentation methods are used as a complement. The data analysis used is product moment correlation data analysis. The results of data analysis obtained r count of 0.708. When consulted with r table level of confidence interval of product moment, then r count is greater than r table of confidence interval level of 5% = 0.266 and at interval level of 1% = 0.345. Therefore, it can be stated that the work hypothesis (Hi) which states the influence of expository learning strategies on students' understanding of the subject of aqidah akhlak class VIII MTs. An-Najah I Karduluk Sumenep academic year 2016/2017, is accepted. Meanwhile, the null hypothesis (H0) states that there is no influence of expository learning strategies on students' understanding of the aqidah akhlak class VIII MTs. An-Najah I Karduluk Sumenep academic year 2016/2017, rejected. So the results of the data analysis above, state that there is an influence of expository learning strategies on student understanding in the subject of aqidah akhlak class VIII MTs. An-Najah I Karduluk Sumenep academic year 2016/2017, the magnitude of which is included in the Strong category.